Effect of Token Economy on Academic Achievement of Secondary School Students: Implications for Counselling - Ihiegbulem, Orji Tobias; Ihiegbulem, Victoria Nkechi; Igwebuike, Dimkpa (Richtmann Publishing, 2011)
The study centered on determining the effect of token economy on academic achievement of secondary schoolstudents. Demonstration Secondary School, Federal College of Education (Technical), Omoku, Rivers State, Nigeria was usedfor the study. Eighty (80) Junior Secondary 3 Integrated Science students and eighty (80) Senior Secondary 1 Biology studentsmaking up one hundred and sixty (160) students of the chosen school, during the 2009/2010 academic session constituted thestudy sample. Each level of students taught by the same teacher was divided into experimental and control groups. Theexperimental groups were motivated with token economy during the lessons while the control groups were not motivated. Rawscores of the students from the two tests they were given made up data for the study. Data analysis involved the use of meanscores and t-test of significant difference between two independent group mean scores, supported by F-test of homogeneity oftwo independent group variances. It was found out that the experimental groups put up higher academic achievement than thecontrol groups. It was also found out that token economy had significant effect on academic achievement of the experimentalgroups. These findings and their counseling implication were discussed